Additional Haptic Information Provided by Anchors Reduces Postural Sway in Young Adults Less Than Does Light Touch - Moraes, Renato; Bedo, Bruno L. S.; Santos, Luciana O.; Batistela, Rosangela A.; Santiago, Paulo R. P.; Mauerberg-deCastro, Eliane [UNESP] (Frontiers Media Sa, 2018)
This study investigated the effect of adding haptic information to the control of posture, as well as comparing the effect of both the light touch (LT) and anchor system (AS) paradigms on postural sway. Additionally, it compared the effect of location and number of points of contact to the control of posture in young adults. The location consisted of using the anchors tied to the finger and held by the hands, and, for LT, the fingertip. For the number of points of contact, participants used two hands, and then separately the dominant hand, and the non-dominant hand, for both anchor and LT paradigms. Participants stood upright with feet-together and in tandem position while performing tasks that combined the use of anchors and LT, points of contact (hand grip and finger), and number of points of contact (two hands and one hand). In this study, the anchors consist of holding in each hand a flexible cable with the other end attached to the ground. The LT consists of slightly touching a rigid surface with the tip of the index finger. The results showed, first, that the anchors improved postural control less than did the LT. Second, they revealed that holding the anchors with the hands or with them tied to the fingertip resulted in a similar reduction in postural sway only in the tandem position. For the feet-together position, the anchors tied to the fingertip were ineffective. Similarly, the use of one or two hands did not affect the contribution of the anchors. However, using two hands in the LT condition was more effective than was one hand. Third, our results showed the presence of a temporal delay between force and center-of-pressure (COP) for the anchors, only in the AP direction with feet-together. In conclusion, overall, the anchors were less effective in reducing postural sway than was the LT. The anchors attached to fingertips were as effective as the hand-held anchors in the tandem position, yet ineffective during foot-together standing. Force-COP timing explains reduced postural sway with LT but not for the anchor; hence, exploratory and supra-postural components may be involved.
Keywords: postural control; balance; haptic cue; foot position; stability